2020
DOI: 10.1186/s12884-020-2823-4
|View full text |Cite
|
Sign up to set email alerts
|

Why do pregnant women in Iringa region in Tanzania start antenatal care late? A qualitative analysis

Abstract: Background: When started early in pregnancy and continued up till childbirth, antenatal care (ANC) can be effective in reducing adverse pregnancy outcomes. While the proportion of women who attend ANC at least once in low income countries is high, most pregnant women attend their first ANC late. In Tanzania, while over 51% of pregnant women complete ≥4 visits, only 24% start within the first trimester. This study aimed to understand the factors that lead to delay in seeking ANC services among pregnant women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
5
22
0
1
Order By: Relevance
“…Behavior of a few of the health workers and how they treat pregnant women was termed as harsh, rude and abusive, which is a massive inconvenience while attending ANC. This is similar to findings in Ethiopia and Tanzania [ 46 , 47 ]. Evidence has shown that a recommendation from a health care professional for vaccination is the most important factor in decision-making for uptake of a maternal vaccine [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Behavior of a few of the health workers and how they treat pregnant women was termed as harsh, rude and abusive, which is a massive inconvenience while attending ANC. This is similar to findings in Ethiopia and Tanzania [ 46 , 47 ]. Evidence has shown that a recommendation from a health care professional for vaccination is the most important factor in decision-making for uptake of a maternal vaccine [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…As much as the healthcare workers would like to maintain a high vaccine coverage, issues such as delays in vaccine delivery to the health facilities meant that even when mothers showed up and demanded to be vaccinated the vaccines were out of stock, causing a missed opportunity. Similar to what has been found in Ethiopia (Gebremichael et al 2018), Tanzania (Maluka et al 2020) and Uganda (Kajungu et al 2020), we observed that if a health care worker was harsh, abusive or rude, it could discourage women from attending ANC clinics, which has a ripple effect on uptake of vaccines by the mothers.…”
Section: Discussionsupporting
confidence: 85%
“…Our analysis points to the importance of adequate investments in infrastructure for intermediate secondary-level referral facilities ( Mwangome et al , 2017 ). For instance, there is compelling evidence the rural and mountainous Kilolo district saw few funds allocated to construction and maintenance of secondary and tertiary facilities, to means of transportation ( Kigume and Maluka, 2018b ) and staffing ( Maluka et al , 2020 ). Consequently, an FBO-managed hospital is designated as district referral hospital, which may discourage attendance of poor households imposing user fees, contrary to public facilities ( Saksena et al , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…These well-known disruptions in the intended referral flows may further discourage access to care due to high travel expenses ( Saksena et al , 2010 ) and specific cultural policies, e.g. spouse accompany ( Maluka et al , 2020 ). Lastly, health facilities located close to district borders—or in districts that do not have a tertiary-level facility—naturally refer patients to other facilities located in neighbouring district not included in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation